Guide to participatory tools for forest communities - Evans, K.; Jong, W. de; Cronkleton, P.; Sheil, Douglas; Lynam, T.; Kusumanto, T.; Colfer, C.J.P. (Center for International Forestry Research, 2006)
The Center for International Forestry Research has developed and adapted various participatory tools for use with forest communities and other natural resource dependent groups. The tools have diverse applications: stakeholder identification, decision making, planning, conflict management, information collection, landscape assessment and other uses. The Guide to Participatory Tools for Forest Communities is intended for environment and development practitioners, researchers and local government officials. It provides information on various tools to help readers grasp basic capabilities, identify the most appropriate tool for their needs and find resources for additional information. Much like a map, this guide sends readers in the right direction when selecting participatory tools.